2017
DOI: 10.1155/2017/4862861
|View full text |Cite
|
Sign up to set email alerts
|

L-Glutamine Supplementation Alleviates Constipation during Late Gestation of Mini Sows by Modifying the Microbiota Composition in Feces

Abstract: Constipation occurs frequently in both sows and humans, particularly, during late gestation. The microbial community of the porcine gut, the enteric microbiota, plays a critical role in functions that sustain intestinal health. Hence, microbial regulation during pregnancy may be important to prevent host constipation. The present study was conducted to determine whether L-glutamine (Gln) supplementation improved intestinal function and alleviated constipation by regulation of enteric microbiota. 16S rRNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…A study in weaning mice demonstrated that dietary glutamine decreased the content of Firmicutes in the jejunum and ileum, and decreased the Firmicutes-to-Bacteroidetes ratio in the ileum (194). Similar findings are reported in studies in adult pigs and human (195,196). In weaning rabbits, dietary glutamine specifically reduced the presence of Clostridium spp.…”
Section: Impact Of Glutamine On the Gut Microbiota Compositionsupporting
confidence: 71%
See 1 more Smart Citation
“…A study in weaning mice demonstrated that dietary glutamine decreased the content of Firmicutes in the jejunum and ileum, and decreased the Firmicutes-to-Bacteroidetes ratio in the ileum (194). Similar findings are reported in studies in adult pigs and human (195,196). In weaning rabbits, dietary glutamine specifically reduced the presence of Clostridium spp.…”
Section: Impact Of Glutamine On the Gut Microbiota Compositionsupporting
confidence: 71%
“…in the ileum, of which colonization in early life has been associated with increased risk of allergic diseases (197,198). Finally, a glutamine-enriched diet is also shown to increase the abundance of beneficial Bifidobacteria in the jejunum of healthy weaned mice (194), and to decrease potentially harmful microorganisms in adult pigs (196). The mechanisms underlying the effects of glutamine on the gut microbiota composition are poorly understood.…”
Section: Impact Of Glutamine On the Gut Microbiota Compositionmentioning
confidence: 99%
“…Interestingly, dietary supplementation of arginine (Arg) in healthy mice decreased the Firmicutes to Bacteroidetes ratio in the small intestine, mainly due to an increase in Bacteroidetes (190). Similarly, dietary supplementation of Gln decreased the Firmicutes/Bacteroidetes ratio in sows (191). Whether modulation of Gln and Arg intake can restore the aberrant Firmicutes/Bacteroidetes ratio observed in ASD patients, and subsequently improve their immune status remains to be examined.…”
Section: The Interaction Between Amino Acids and The Gut Microbiome Imentioning
confidence: 99%
“…Glutamine supplementation is beneficial in improving disease symptoms and intestinal structure and barrier function [ 72 , 73 ]. This amino acid can increase intestinal-friendly microbiota ( Bacteroidetes and Actinobacteria ), while decrease pernicious bacteria ( Oscillospira and Treponema ) [ 74 ]. Its role in IBD is controversial [ 72 , 75 , 76 , 77 , 78 ], but the results of most glutamine studies support further evaluation as a potential therapeutic agent.…”
Section: Potential Roles Of Amino Acids In Ibdmentioning
confidence: 99%